New Frontiers in Molecular Imaging Using Peptide-Based Radiopharmaceuticals for Prostate Cancer - Li, Xin; Cai, Huawei; Wu, Xiaoai; Li, Li; Wu, Haoxing; Tian, Rong (Frontiers in Chemistry, 2020)
The high incidence of prostate cancer (PCa) increases the need for progress in its diagnosis, staging, and precise treatment. The overexpression of tumor-specific receptors for peptides in human cancer cells, such as gastrin-releasing peptide receptor, natriuretic peptide receptor, and somatostatin receptor, has indicated the ideal molecular basis for targeted imaging and therapy. Targeting these receptors using radiolabeled peptides and analogs have been an essential topic on the current forefront of PCa studies. Radiolabeled peptides have been used to target receptors for molecular imaging in human PCa with high affinity and specificity. The radiolabeled peptides enable optimal quick elimination from blood and normal tissues, producing high contrast for positron emission computed tomography and single-photon emission computed tomography imaging with high tumor-to-normal tissue uptake ratios. Owing to their successful application in visualization, peptide derivatives with therapeutic radionuclides for peptide receptor radionuclide therapy in PCa have been explored in recent years. These developments offer the promise of personalized, molecular medicine for individual patients. Hence, we review the preclinical and clinical literature in the past 20 years and focus on the newer developments of peptide-based radiopharmaceuticals for the imaging and therapy of PCa.